Abigail: The Wise Woman of Carmel - Carman, Amy Smith (Stone-Campbell journal, 2015)
Abigail's wise and independent intervention to avert the impending disaster sparked by her foolish husband saves herself and her household from slaughter and Israels future king from presumption and bloodguilt. An examination of the 1 Samuel 25 narrative concerning Abigails prophetic act of mediation, which draws Davids gratitude and Yahwehs blessing, contributes to the understanding of the role women played in ancient Israel.